2006
DOI: 10.1152/ajpheart.00148.2006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of in-stent restenosis by oral copper chelation in porcine coronary arteries

Abstract: .-Stress-induced release of IL-1␣ and fibroblast growth factor-1 is dependent on intracellular copper and is a major driver of neointimal hyperplasia. Therefore, we assessed the effect of tetrathiomolybdate (TTM), a clinically proven copper chelator, on in-stent restenosis. Nine pigs were treated with TTM (5 mg/kg po) twice daily for 2 wk before stent implantation and for 4 wk thereafter, and nine pigs served as controls. In-stent restenosis was assessed by quantitative coronary angiography (QCA), intravascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Additionally, TM downregulates the number of macrophages, as well as FGF1, S100A13, and IL1α levels in carotid artery walls. It was also found that TM inhibits in‐stent restenosis in porcine coronary arteries [Mandinov et al, 2006], These data suggest that inhibition of the non‐classical release of FGF1 and IL1α by Cu 2+ chelation may represent a promising approach to the management of restenosis. More recently, it was demonstrated that in rats TM blocks the development of antigen‐induced arthritis, a pathology that involves IL1 [Omoto et al, 2005].…”
Section: Biomedical Significance Of Non‐classical Fgf1 and Il1α Releasementioning
confidence: 95%
“…Additionally, TM downregulates the number of macrophages, as well as FGF1, S100A13, and IL1α levels in carotid artery walls. It was also found that TM inhibits in‐stent restenosis in porcine coronary arteries [Mandinov et al, 2006], These data suggest that inhibition of the non‐classical release of FGF1 and IL1α by Cu 2+ chelation may represent a promising approach to the management of restenosis. More recently, it was demonstrated that in rats TM blocks the development of antigen‐induced arthritis, a pathology that involves IL1 [Omoto et al, 2005].…”
Section: Biomedical Significance Of Non‐classical Fgf1 and Il1α Releasementioning
confidence: 95%
“…CP contains copper, and accounts for 95% of the total circulating copper in adults. The copper chelator tetrathiomolybdate (TTM) given twice daily for 2 weeks before coronary stent implantation in pigs, and for 4 weeks thereafter, reduced the extent of restenosis by 39%, and this effect was associated with a reduction of 70% in serum CP [238]. In another study, Mandinov et al [239] reported that TTM treatment produced a 60% reduction in neointimal hyperplasia in balloon injured carotid artery in rats.…”
Section: Pleiotropic Effects Of Statinsmentioning
confidence: 99%
“…Mandinov et al . also found that ISR could be inhibited directly by oral copper chelation in porcine coronary 27 . Thus, the beneficial influence of Cu ions on reduction of ISR was well recognized in the coronary field.…”
Section: Introductionmentioning
confidence: 78%